Pendalaman Materi Dan Transfer of Knowledge Bidang MIPA-I Bagi Guru MGMP SMA Kota Metro, Lampung - Gregorius Nugroho Susanto; Roniyus Marjunus; Aang Nuryaman; Febi Eka Febriansyah; Nida Lidya Susanti (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Quality Education is one of the 17 goals of the Sustainable Development Goals (SDGs) 2030 launched by the United Nations in 2015. The teaching of Physics, Biology, Mathematics, and Informatics (MIPA-I) at the senior high school level constitutes an essential component of this goal. Adequate student understanding of MIPA-I is necessary to reduce the perception of these subjects as difficult and to prepare students for higher education. Such understanding is strongly influenced by teachers’ mastery of subject content and instructional methods. Therefore, improving the quality of content and knowledge transfer strategies among MIPA-I teachers, particularly in Lampung Province and Metro City, is of critical importance. A teacher development program involving members of the Senior High School Subject Teacher Forum (MGMP) of Metro City was implemented to enhance teachers’ competencies in delivering instructional materials, as indicated by an 85% increase in post-test scores compared to pre-test results.